PENERAPAN PEMBELAJARAN BERBASIS STEM UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI SISTEM KOLOID DI SMA NEGERI 2 TOMOHON - Butar Butar, Gabryella Damayanti; Palilingan, Septiany Ch; Gumolung, Dokri (LPPM Politeknik Saint Paul Sorong, 2024)
This research aims to determine the application of STEM-based learning in improving student learning outcomes in colloid system subjects at SMA Negeri 2 Tomohon. This research is Class Action (Class Action Research). The subjects in this research were 12 students in class XI MIA of SMA Negeri 2 Tomohon. This research includes 4 stages: (1) planning stage, (2) implementation, (3) observation, (4) reflection. The data collection methods used in this research are observation, interviews and post-test methods. The results of the research show that with the application of the STEM method, student learning outcomes increased, namely from cycle I 73.91%, in cycle II with improvements in actions in the form of group division, carrying out colloid system project practicum, with guidance from start to finish in practicum activities, then there was an increase from 73.91% (cycle I) to 86% (cycle II).